2014
DOI: 10.1103/physrevb.90.125316
|View full text |Cite
|
Sign up to set email alerts
|

Orbital magnetic ratchet effect

Abstract: Magnetic ratchets -two-dimensional systems with superimposed non-centrosymmetric ferromagnetic gratings -are considered theoretically. It is demonstrated that excitation by radiation results in a directed motion of two-dimensional carriers due to pure orbital effect of the periodic magnetic field. Magnetic ratchets based on various two-dimensional systems like topological insulators, graphene and semiconductor heterostructures are investigated. The mechanisms of the electric current generation caused by both r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Finally we note, that while here we have dealt with a homogeneous magnetic field, the observed ratchet photocurrent in superlattices made of hard magnetic material (Dy) opens a possibility to study the ratchet effect driven by an inhomogeneous periodic magnetic field recently suggested in Refs. [33,45]. This kind of experiments would apply remnant magnetization of Dy together with the enhanced magnetic properties of DMS QWs and is a future task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally we note, that while here we have dealt with a homogeneous magnetic field, the observed ratchet photocurrent in superlattices made of hard magnetic material (Dy) opens a possibility to study the ratchet effect driven by an inhomogeneous periodic magnetic field recently suggested in Refs. [33,45]. This kind of experiments would apply remnant magnetization of Dy together with the enhanced magnetic properties of DMS QWs and is a future task.…”
Section: Discussionmentioning
confidence: 99%
“…The DGG structure of sample 4 has been fabricated by depositing 75-nm-thick Dy and 15-nm-thick Au films. Premagnetizating the hard magnetic Dy-based superlattice enables realization of a magnetic ratchet which features an inhomogeneous magnetic field, recently suggested in [33,45].…”
Section: B Dual Grating Top Gate Structurementioning
confidence: 99%
“…The magnetic ratchet effect is a generic feature of inversionasymmetric two-dimensional systems [1][2][3][4][5][6][7][8]. It consists of the production of a dc electric current in response to a steady in-plane magnetic field B and an alternating electric field E, in the presence of inversion asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic quantum ratchet effect has also been treated theoretically for bi‐layer graphene and graphene superimposed by an asymmetric lateral superlattice . The former work considered the orbital effect of an in‐plane magnetic field on electrons in bilayer graphene, deriving linear‐in‐field contributions to the low‐energy Hamiltonian arising from the presence of either skew interlayer coupling or interlayer potential asymmetry.…”
Section: Magnetic Quantum Ratchet Effectmentioning
confidence: 99%